Leaf area index, evapotranspiration and dry Bio-mass of maize (Zea mays L.) - CHOWDHURY, A.; DAS , H. P.; GAONKAR, S. B. (MAUSAM, 1992)
Based on the crop season data for the years 1989 and 1990, LAI, biomass, water use efficiency, soil evaporation, potential and actual plant transpiration have been determined for maize. The ET/EP ratio has been correlated with LAI and dry biomass. Correlations were also determined between some of the above crop characteristic factors as also with moisture in topsoil profile. The analysis indicated that total rainfall during crop season does not have large bearing on the maize yield. The water use efficiency appears to be nearly independent of atmospheric demand. Actual and potential plant transpirations and the evaporation from the soil could be computed from a simple model.